Profiling of cytokines, chemokines and growth factors in saliva and gingival crevicular fluid. (June 2021) - Liu, Yong; Zhao, Renping; Reda, Bashar; Yang, Wenjuan; Hannig, Matthias; Qu, Bin
Highlights: Cytokine profiles in saliva and GCF stay stable under healthy conditions. Cytokine profiles are highly individualized in saliva but not in GCF. Our findings suggest that cytokines in saliva and GCF may have different origins. Abstract: In saliva and gingival crevicular fluid (GCF) soluble factors such as cytokines, chemokines and growth factors have shown a great potential serving as biomarkers for early detection and/or diagnosis of oral and systemic diseases. However, GCF and saliva, which one is a better source is still under debate. This study aimed to gain an overview of cytokines, chemokines and growth factors in saliva and GCF to pave the way for selecting suitable oral fluids for oral and systemic diseases. Multiplex cytokine assay was conducted to determine concentrations of cytokines, chemokines and growth factors in saliva and GCF samples from healthy subjects. The protocol for sample collection was carefully optimized. Stabilization, repeatability, and donor variation of the profiles were analyzed. We found that for different donors, cytokine and chemokine profiles showed unique patterns in saliva but similar patterns in GCF. In terms of growth factors, the profiles were individualized in saliva and GCF. All profiles stayed stable for the same healthy individual. In saliva, profiles of cytokines, chemokines and growth factors are individualized for different donors. In GCF, profiles of cytokines and chemokines are similar. Other factors, such as growth factors and T helper-related cytokines, are highly variable in donors. Profiles of soluble factors are not correlated in saliva and GCF. The comprehensive cytokine profiles in saliva and GCF reported in this work would serve as a good base for choosing promising cytokines for developing biomarkers in oral fluids.